THE EFFECTIVENESS OF PICTURE SERIES IN TEACHING WRITING RECOUNT TEXT - Glorya Agape Montang; Mister G. Maru; Delli Sabudu (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
The purpose of this research is to know whether using picture series is effective in teaching writing recount text. The writer conducted the study at the tenth years students of SMA Negeri 1 Remboken at the 2022/2023 year of academic. The research design used was an experimental design with a quantitative approach, Pre-test, treatment, and post-test procedures were used in this pre-experimental study. A test (pre-test and post-test) with a writing exercise connected to retelling about a holiday was the instrument utilized in this study. The participants in this study were the students of SMA Negeri 1 Remboken. 28 students from class X A served as the research samples. The findings results show that The pre-test mean score was 63.21, and the post-test mean score was 92.75. The mean score on the post-test was higher than it was on the pre-test. The results of the investigation showed that the difference between the 14.500 in Tcount and the 2.052 in Ttable was significant at 5%. This outcome served as proof that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, using image series significantly improved the tenth-year students' recount narrative writing at SMA Negeri 1 Remboken.